2016
DOI: 10.1063/1.4967555
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing flow steadiness in laminar boundary layer shock interactions

Abstract: The Direct Simulation Monte Carlo method has been used to model laminar shock wave boundary interactions of hypersonic flow over a 30/55-deg double-wedge and "tick-shaped" model configurations studied in the Hypervelocity Expansion Tube facility and T-ADFA free-piston shock tunnel, respectively. The impact of thermochemical effects on these interactions by changing the chemical composition from nitrogen to air as well as argon for a stagnation enthalpy of 8.0 MJ/kg flow are investigated using the 2-D wedge mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In Ref. 10, it was concluded that the relative magnitude of the specific heat ratio has a significant impact on the SWBLI (Shock Wave/Boundary Layer Interaction). Specifically, the flow of argon resulted in a separation bubble with 1.8 times the size of the one for nitrogen and, due to the endothermic effects of finite-rate chemistry, the size of this region was 1.5 times smaller for air than for nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. 10, it was concluded that the relative magnitude of the specific heat ratio has a significant impact on the SWBLI (Shock Wave/Boundary Layer Interaction). Specifically, the flow of argon resulted in a separation bubble with 1.8 times the size of the one for nitrogen and, due to the endothermic effects of finite-rate chemistry, the size of this region was 1.5 times smaller for air than for nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, larger aft angles lead to a larger standoff distance of the bow shock, higher probability of shock impingement on the wall and overall increasing complexity of the interaction mechanism, potentially leading to instability of the shear layers or unsteady interaction patterns [5,8]. Efforts have also been made in the attempt to better understand the influence of the gas mixture and/or specific heat ratio on the physics of shock interactions [9,10]. Tumuklu et al compared the flow over a 30°-55°double-wedge for three different gas mixtures: air, nitrogen, and argon [9].…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [10], the role of the gas mixture was further investigated. It was concluded that the relative magnitude of the specific heat ratio has a significant impact on SBLI (Shock Boundary Layer Interaction).…”
Section: Introductionmentioning
confidence: 99%